Current trends of european information and library education (LIS) - Shemaieva Hanna; Prilutska Alla; Kysliuk Liubov (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article consists in the coverage of the modern trends in the field of information and library education (LIS) in European countries at the master’s level. Metodology is based on a bibliographic analysis of publications by Ukrainian and foreign researchers dedicated to the training of personnel at the master’s level, monitoring information from the websites of universities in European countries regarding master’s educational programs according to the information-library profile, followed by a comparative analysis of their content. The scientific novelty consists in expanding ideas about trends in information and library education at the master’s levelin European countries. Conclusions. Each country has its own characteristics, but the common feature is the inclusion of components of modern digital tools and technologies both in the library, archival and documentation sectors, and beyond of ones. The trends of interaction in the training of personnel at the master’s level have been established: 1) development of cooperation under common programs at the national level (Austria, Belgium, Spain); 2) strengthening international cooperation (Italy with Estonia and Norway; Great Britain together with Portugal; Denmark, Greece with Great Britain); 3) the powerful movement of iSchools as interdisciplinary or transdisciplinary structures in universities, which are characterized by the expansion of the spectrum of programs and the focus on optional disciplines and the spread of international cooperation.